Study the Association of CYP3A5 Polymorphism on the Risk of Breast Cancer in Some of the Iraqi Women - Israa Hussein Hamzah (Journal of Global Pharma Technology, 2018)
Cytochrome P450 enzymesare involved in activation of numerouspro carcinogenic compounds such as polycyclic aromatic hydrocarbon as well as plenty of endogenous compounds including testosterone and estrogen. The CYP3A isoenzymes represent the predominant cytochrome P450 enzymes in the human liver and gastrointestinal tract. CYP3A subfamily have four members (CYP3A43, CYP3A7, CYP3A5 and CYP3A4). The aim of the present work is to investigate whether the CYP3A5 polymorphism modifies the risk of breast cancer in the Iraqi population. A total of eighty women were recruited in the present study divided into fifty breast cancer patients aged 25-65 years who visit the Oncology Teaching Hospital, Baghdad, Iraq, as well as 30 healthy sex and age matched controls. The sequence analysis of CYP3A5 fragment with molecular weight 349bp resulted in two distinct genotypesin the breast cancer group, with 96% (n=48) had the CYP3A5*3/*3 homozygote genotype and 4% (n=2) had the CYP3A5*1/*3 heterozygote genotype. In the control group, 100 %( n=30) had the CYP3A5*3/*3 homozygote genotype. No significant differences between breast cancer patients and control were observed with respect to genotype distribution (P>0.05). Our results revealed that there is no association between risk of the breast cancer and CYP3A5 polymorphism in Iraqi women.Keywords: Cytochrome, CYP3A5, Iraq, Breast cancer, Polymorphism